Prelacteal feeding of neonants & discardation of first breast milk Among recently delivered women of Uttar Pradesh, India - Tripathy, Dr. Tridibesh; Tripathy, Anjali; Dwivedi, Dr. Rakesh; Gautam, Dr. Mohini; Prusty, Dr. Umakant; Nayak, Dr. Chintamani (Jour Med Resh and Health Sci, 2020)
When ASHAs were introduced in NRHM in 2005, their primary aim was to visit homes of newborns as the first program in UP operated through the ASHAs was the Comprehensive Child Survival Program in 2008. Since then, tracking of all deliveries and all the newborns are an integral part of the work of ASHAs in all the primary health care programs operated by the NHM in UP (GOI, 2005, GOUP, 2013). The current article examines the role & work of ASHAs through the responses of the mothers of newborns at district level. Evaluation studies on the performance of ASHAs was done since 2011 as by then ASHAs had actually worked in the field for a minimum period of 5 years. It is to be noted that National Rural Health Mission was rolled out in April 2005 but it took about one to two years for the states to hire ASHAs and put things in place right from the state to the village level (GOUP, 2013). In this article, a comprehensive feedback is elicited from the Recently Delivered Women on the pre-lacteal feeding of their newborns as part of newborn care program at the district level. The current study explores some of the crucial variables on the home-based newborn care activities like the poor practice of pre-lacteal feeding of the newborn through the response of mothers of newborns on newborn care. The poor practice of pre-lacteal feeding of newborn in child health programs is a critical barrier in breastfeeding practices. The current article follows up the role of ASHAs in Home Based Newborn Care program through the response of the mothers on the type of pre-lacteals & discarding of milk before breastfeeding the child. The mothers were selected as respondents as they were the selected mothers from the list of mothers available with their ASHAs at the time of survey. The relevance of the study assumes significance as data on the details of the type of pre-lacteal feeding of newborn as a barrier component of child health & newborn programs are not included in many surveys. Further, response details from the mothers on these options on pre-lacteals where their types are discussed are usually not collected in many studies/surveys. Such responses that collect actual actions on the pre-lacteal feeding & milk discarding before breastfeeding are not collected in many surveys. Such information collection there by indirectly assess the work & approach of ASHAs including the awareness of ASHAs & mothers on the programs related to Early Initiation of Breastfeeding (EIBF) are not the focus in very large-scale health surveys. Similarly, such response on these two barriers on EIBF related activities of newborn care through the work of ASHAs in the current implemented programs do not come under the ambit of many social studies or surveys. The surveys gain more valency when the response is solicited from the horse’s mouth like the current article. A total of four districts of Uttar Pradesh were selected purposively for the study and the data collection was conducted among the mothers in the respective districts. A pre-tested structured & in-depth interview schedule was used with close-ended questions. These in-depth interview schedule collected descriptive details as responded by mothers. The quantitative data were conducted amongst the mothers and a total of 500 respondents participated in the study. The results reflected that majority of the RDWs in Banda, Barabanki and Saharanpur district and about 94% in Gonda had given milk other than breast milk to their newborn as pre-lacteal feed. Next barrier as an activity was discarding of milk before breastfeeding the child. About 10% in Banda, more than 5% in Barabanki 7 less than 5% of RDWs in the rest two districts replied that they discarded the first milk from their breast before the newborn is put to the breast for the first time.